Pressure driven spin transition in siderite and magnesiosiderite single crystals. Issue 1 (December 2017) - Weis, Christopher; Sternemann, Christian; Cerantola, Valerio; Sahle, Christoph; Spiekermann, Georg; Harder, Manuel; Forov, Yury; Kononov, Alexander; Sakrowski, Robin; Yavaş, Hasan; Tolan, Metin; Wilke, Max
Abstract Iron-bearing carbonates are candidate phases for carbon storage in the deep Earth and may play an important role for the Earth's carbon cycle. To elucidate the properties of carbonates at conditions of the deep Earth, we investigated the pressure driven magnetic high spin to low spin transition of synthetic siderite FeCO3 and magnesiosiderite (Mg0.74 Fe0.26 )CO3 single crystals for pressures up to 57 GPa using diamond anvil cells and x-ray Raman scattering spectroscopy to directly probe the iron 3d electron configuration. An extremely sharp transition for siderite single crystal occurs at a notably low pressure of 40.4 ± 0.1 GPa with a transition width of 0.7 GPa when using the very soft pressure medium helium. In contrast, we observe a broadening of the transition width to 4.4 GPa for siderite with a surprising additional shift of the transition pressure to 44.3 ± 0.4 GPa when argon is used as pressure medium. The difference is assigned to larger pressure gradients in case of argon. For magnesiosiderite loaded with argon, the transition occurs at 44.8 ± 0.8 GPa showing similar width as siderite. Hence, no compositional effect on the spin transition pressure is observed. The spectra measured within the spin crossover regime indicate coexistence of regions of pure high- and low-spin configuration within the single crystal.